WOMEN’S NEEDS VS. ECONOMIC SURVIVAL DURING THE COVID-19 PANDEMIC: NAVIGATING THIS TENSION USING CARE AND JUSTICE - S.A. Puen; R.J.M. Sanchez (Acta Theologica)
Women are among the many vulnerable groups that are severely affected by the pandemic: All over the world, women have been hit harder by the pandemic, leading some to call the global recession a “shecession”. “Shecession” refers to “the disproportionate impact of a pandemic recession on working women”, which leads to greater gender inequality. Working women have been gravely affected by the pandemic, but their situation is often justified as “necessary” in helping businesses survive. We argue for a caring justice framework, using Fratelli Tutti and care ethics in navigating the tensions between the individual and the community, analysing and transforming the way in which work is structured in the Philippines at present.